Attracting consumers in the thriving cosmeceuticals market: A new innovation breakthrough. Issue 8 (8th July 2014) - Phaiboon-udomkarn, Bongkot; Josiassen, Alexander
Abstract : Purpose: – The purpose of this study is to analyze and mitigate consumers' perceived risk in purchasing cosmeceutical products. The lucrative market of cosmeceuticals has motivated many cosmetics and pharmaceutical companies to rethink their existing product lines to gain a strong foothold in cosmeceuticals industry. It is important that these corporates are taking note and scrambling to integrate their marketing activities to gain a foothold in this emerging sector. Design/methodology/approach: – A questionnaire set was created to survey among 473 consumers, using cosmeceutical skincare products as a product group. The risk mitigation and assessment are investigated to understand consumers' final decision on whether or not to purchase a product. Findings: – Results indicate that positive expert opinion reduces consumer risk perception, better product-country image can minimize consumer's perceived risk and strong brand image lowers perceived risks of consumer. Practical implications: – Practitioners should have a close examination of the product-country image and brand images, as well as an advantageous use of expert opinions – all of which may affect the consumer's willingness to buy and lower perceived risks associated with the product. Originality/value: – This study enhances the limited research in the new field of pharmaceuticals, which also leads to a better understanding of risk mitigation and factors driving consumers' willingness to buy a healthcare product.